PREVALENCE AND RISK FACTORS OF THE ISCHEMIC HEART DISEASES IN INDONESIA: A DATA ANALYSIS OF INDONESIA BASIC HEALTH RESEARCH (RISKESDAS) 2013 - Suryati, Tati; Suyitno, Suyitno (Public Health of Indonesia, 2020)
Background: The Cardiovascular disease (CVDs) is leading in the world as a number one cause of death.  Ischemic Heart Disease (IHD) part of CVDs which is often also called coronary artery disease.Objective: The purpose this study is to know the risk factors for ischemic heart disease in Indonesia, 2013.Methods: The risk assessment analyzes was used to exam the risk factor IHD around 721,427 people from data of Basic Health Research (RISKESDAS) 2013 in Indonesia.Results: The finding of this study was former smoker (Adj. OR= 4.09, 95% C.I=3.78-4.43), hypertension (Adj. OR= 3.80, 95% C.I=3.60-4.10), obesity (Adj. OR= 1.96, 95% C.I=1.84-2.08), low consumption of fruits and vegetables (Adj. OR= 0.70, 95% C.I=0.57-0.87), and low physical activity (Adj. OR= 1.14, 95% C.I=1.06-1.23) are risk factor of IHD in Indonesia, 2013.Conclusion: The central, regional, and even village level special attention have a need for reducing IHD. Cross-program and sector collaboration are also needed collaboration with NGOs and the private sector to control risk factors outside the health sector and improve the environment.